Deletions and insertions within an amino-terminal domain of pp60v-src inactivate transformation and modulate membrane stability. - Wang, H C (1989)
We previously showed (V. W. Raymond and J. T. Parsons, Virology 160:400-410, 1987) that variants of the Prague A strain of Rous sarcoma virus containing large deletions impinging on a region of the src gene encoding amino acid residues 143 to 169 were defective for transformation of chicken cells in culture. Here we report that introduction of small (tri-and tetrapeptide) deletions into a region of pp60v-src containing amino acid residues 155 to 175 was found to inactivate transformation. In addition, insertion of four, but not one, amino acid residues at position 161 also inhibited transformation. Biochemical analysis of the src proteins encoded by individual transformation-defective variants revealed that the structural alterations introduced into this domain had only marginal effects upon src tyrosine-specific protein kinase activity. However, the src proteins encoded by defective variants exhibited a significantly shorter half-life within the cell, although these proteins efficiently and rapidly associated with cellular membranes. Our results suggest that the structural domain encompassing residues 155 to 177 may influence the stability of pp60src in the cellular membrane, possibly via the interaction of src with a cellular membrane component(s) or substrate(s).